2021
DOI: 10.1021/acsami.1c12653
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Defect Hydrated Vanadium Dioxide/Graphene as a Superior Cathode for Aqueous Zn Batteries

Abstract: Zinc ion batteries have become a new type of energy storage device because of the low cost and high safety. Among the various cathode materials, vanadium–oxygen compounds stand out due to their high theoretical capacity and variable chemistry valence state. Here, we construct a 3D spongy hydrated vanadium dioxide composite (Od-HVO/rG) with abundant oxygen vacancy defects and graphene modifications. Thanks to the stable structure and abundant active sites, Od-HVO/rG exhibits superior electrochemical properties.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 61 publications
1
33
0
Order By: Relevance
“… Structural modification and composite of cathode materials: (A) Crystal structures of bulk MoS 2 and MoS 2 /graphene; (B,C) the corresponding migration energy barriers with the variation of the MoS 2 -to-graphene distance; (D) schematic illustration of freestanding CNT/MnO 2 -PPy; (E) schematic diagram of Zn 2+ (de)intercalating mechanism in O d -HVO/rG; (F) illustration of electron/ion transport and ion diffusions across the electrodes of CNT@KMO@GC. Reproduced with permission ( Zhang et al, 2020a ; Li et al, 2021d ; Huang et al, 2021 ; Wang et al, 2021 ). …”
Section: Stability Optimizations For Cathode Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“… Structural modification and composite of cathode materials: (A) Crystal structures of bulk MoS 2 and MoS 2 /graphene; (B,C) the corresponding migration energy barriers with the variation of the MoS 2 -to-graphene distance; (D) schematic illustration of freestanding CNT/MnO 2 -PPy; (E) schematic diagram of Zn 2+ (de)intercalating mechanism in O d -HVO/rG; (F) illustration of electron/ion transport and ion diffusions across the electrodes of CNT@KMO@GC. Reproduced with permission ( Zhang et al, 2020a ; Li et al, 2021d ; Huang et al, 2021 ; Wang et al, 2021 ). …”
Section: Stability Optimizations For Cathode Materialsmentioning
confidence: 99%
“…The optimization strategy of combination engineering usually includes carbon-based materials, which can improve the electron transmission efficiency and structural stability of materials ( Yang et al, 2021 ; Zeng et al, 2021 ). Hou et al synthesized a 3D reticular graphene-based hydrated vanadium dioxide composite (O d -HVO/rG) with abundant oxygen vacancies using the solvothermal method ( Huang et al, 2021 ). The research confirmed that oxygen vacancy defects can provide more active sites and promote the reversibility of the reaction, while the highly conductive and robust rG sponge can promote electron migration and reduce the accumulation of O d -HVO to improve the conductivity and structural stability, as shown in Figure 2E .…”
Section: Stability Optimizations For Cathode Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 146,147 ] Hou and colleagues used a hydrothermal method to create a 3D graphene‐sponge hydrated vanadium dioxide (HVO) composite ( Figure a) after considering the earlier concern. [ 148 ] Reduced graphene (rG)‐doped HVO provides both copious oxygen vacancy defects (denoted as O d –HVO/rG) and graphene conducting channels (Figure 14b–d). The oxygen vacancies give additional active locations for zinc ion capacity storage.…”
Section: Interlayer Engineering Regulationsmentioning
confidence: 99%
“…Reproduced with permission. [ 148 ] Copyright 2021, American Chemical Society. The characterizations of VO 2 ·0·2H 2 O nanocuboids anchored on graphene sheets (VOG) composite: g) SEM images and h) TEM images.…”
Section: Interlayer Engineering Regulationsmentioning
confidence: 99%